Impact of biodiesel on injector deposit formation - Liaquat, A.M.; Masjuki, Haji Hassan; Kalam, M.A.; Varman, M. (2012)
Reducing exhaust emissions from CI engines through continued legislative pressure has resulted in the development of advanced fuel injection equipment. This advanced injection system produces higher temperature and pressure at the injector tip which initiates deposit formation at and around the injector. However, in the short term operation, there are many acceptable studies showing good performance results for engines operating with biofuels in literature. In more extended operations, some of the same fuels can cause degradation of engine performance, excessive carbon deposits and actual damage to the engine. In this research work, the endurance test was carried out for 250 h on 2 fuel samples; DF (diesel fuel) as baseline fuel and JB20 (20% Jatropha biodiesel and 80% DF) in a single cylinder CI engine to investigate the effects of JB20 on the injector nozzle deposits and engine lubricating oil. According to the results of the investigations, visual inspection shows that some deposit accumulation appeared on liners of injectors for both fuel samples (DF and JB20). However using Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray spectroscopy (EDX), greater carbon deposits at and around the injector tip were observed in case of JB20. Moreover, the lubricating oil analysis showed excessive wear metal concentrations for JB20 when compared to the engine running with diesel fuel. Viscosity decreased very soon to values below the minimum recommended due to dilution with both fuel samples, but especially more with JB20.